Cultural City Brands And Global Competitiveness - Anatolyevna Pashkus, Natalia (2019)
This article deals with the problem of a city's cultural identity, which allows us to develop a strong city brand and ensure its global competitiveness. The authors analyzed the basic conceptual approaches to identifying a city’s cultural identity. They concluded that the imperial and global level of the city influences the development of its cultural identity and contributes to the growth of its brand value.The authors analyzed the cultural identity of cities, which is essentially based on the imperial role and global prevalence of cultural imperatives. This work shows that cities may not be characterized by the imperial essence and global orientation from throughout their historical development. The imperial essence and global orientation of the city can develop for a certain period of the city’s history. However, when the cultural context changes and its influence in the cultural, economic and social space weakens, the city also loses its imperial or global status.The article also reveals new patterns in the formation of key attributes of a city brand and the development of its cultural identity. The identified patterns are applied in the evaluation of the global competitiveness of a city, within the framework of a breakthrough strategy implementation in the place market. In accordance with the proposed assessment system, a model of city competitiveness was developed and tested in four cities with strong brands and evident cultural identity. These cities also met the requirements for an imperial level of development, globalism, and a breakthrough positioning strategy.Implementation of this model also contributed to the development of new recommendations on the breakthrough positioning of city brands based on their cultural identity, including the imperial essence and globalism of the city.